Paternal migration and children's educational attainment and work activity: the case of Mexico. Issue 4 (8th August 2022) - Song, Qian; Glick, Jennifer
ABSTRACT: Most of the research evaluating the import of paternal migration for children's outcomes has taken 'left-behind children' as a single group. Taking a life course perspective, this paper distinguishes fathers' short-term and long-term migrations, as well as return migration, as they affect children's productive activities. Using the Mexican Family Life Survey (2002–2009), we followed school-aged children from two-parent households in 2002 and observed their activities as they transitioned into adulthood from 2005 through 2009. We found that fathers' short-term migration is negatively associated with children's labor force participation, especially for 12 – to 18-year-old boys, suggesting that paternal migration may interrupt adolescent boys' labor market transition in the short-term. Fathers' long-term migration and return migration does not significantly alter children's activities. However, the negative role of fathers' long-term absence and benefits brought by the paternal migration trip are important mechanisms for educational persistence and the labor force entrance of 12 – to 18-year-old girls, highlighting the conditions under which certain mechanisms may work. This suggests that migration is a family process, with the outcomes lying in the interplay of the stages of migration, children's life stages, and how gender is treated within cultural and familial contexts.